Dermatoglyphics: A Marker of Periodontal Disease (Journal of Orofacial Research, 1970)
Dermatoglyphics is the scientific study of fingerprint patterns. Fingerprints are formed in early embryonic life, during the 10th to 16th weeks of intrauterine life and remain permanent during the whole life. Dermatoglyphics can be used as a diagnostic tool of genetically and nongenetically determined diseases. Thus, it can be used not only in the field of medicine but also in dentistry for the early identification or prediction of oral lesions and diseases. Hence the present paper reviews the application of dermatoglyphics in dentistry along with the advantages, limitations, and patterns of dermatoglyphics.